Medical Imaging 2023: Biomedical Applications in Molecular, Structural, and Functional Imaging 2023
DOI: 10.1117/12.2654091
|View full text |Cite
|
Sign up to set email alerts
|

Development of fast and three-dimensional focused x-ray luminescence tomography system

Abstract: X-ray luminescence computed tomography (XLCT) is a hybrid molecular imaging modality combining the merits of both X-ray imaging (high spatial resolution) and optical imaging (high sensitivity to tracer nanophosphors). Narrow X-ray beam based XLCT imaging has been demonstrated to have the capacity of high spatial resolution imaging at the cost of the data acquisition time. We have primarily focused on improving the performance of the narrow X-ray beam based XLCT imaging. In a previous study, we proposed a scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our experiments have shown that we have achieved good DICE similarity coefficients, especially for the case with four detectors. In future studies, we plan to apply this imaging system in preclinical applications [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments have shown that we have achieved good DICE similarity coefficients, especially for the case with four detectors. In future studies, we plan to apply this imaging system in preclinical applications [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies [15][19], we built a pencil beam based XLCT imaging system with four detectors. In the following numerical simulations, we investigated the effect of detector number up to 16 detectors, while in the physical experimental setup, we only utilized 4 detectors due to the limited resource.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1 shows the schematics of the four- channel XLCT system which was developed from the single-channel XLCT system in our lab [16][15][13]. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation